A constructive Christian theology for the pluralistic world: Author's introduction of the project and a response to reviewers. Issue 4 (7th September 2020) - Kärkkäinen, Veli‐Matti
Abstract: The author of the five‐volume a Christian theology for the pluralistic world (Eerdmans, 2013–2017), Veli‐Matti Kärkkäinen, introduces the nature, distinctive features, and methodology of the project and also responds to the reviewers whose reviews have been included in this issue.